2020
DOI: 10.1063/5.0007092
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field-enhanced beam monitor for ionizing radiation

Abstract: For the microwave cavity resonance spectroscopy based non-destructive beam monitor for ionizing radiation, an addition—which adapts the approach to conditions where only little ionization takes place due to, e.g., small ionization cross sections, low gas pressures, and low photon fluxes—is presented and demonstrated. In this experiment, a magnetic field with a strength of 57 ± 1 mT was used to extend the lifetime of the afterglow of an extreme ultraviolet-induced plasma by a factor of ∼5. Magnetic trapping is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Due to logarithmic plotting in figure 4(a), these apparent negative n e are not visible. Although these negative shifts have been investigated in prior works [9,16], a conclusive explanation of negative shifts of such an extent is absent. Since the effect is beyond the scope of the current study, which focuses on the decay in the higher n e regimes.…”
Section: Plasma Afterglow Decay Timesmentioning
confidence: 91%
See 4 more Smart Citations
“…Due to logarithmic plotting in figure 4(a), these apparent negative n e are not visible. Although these negative shifts have been investigated in prior works [9,16], a conclusive explanation of negative shifts of such an extent is absent. Since the effect is beyond the scope of the current study, which focuses on the decay in the higher n e regimes.…”
Section: Plasma Afterglow Decay Timesmentioning
confidence: 91%
“…These measurements also confirmed that the magnetic field magnitude at the position of the cavity is uniform, taking into account the measurement accuracy. These simulations and measurements were also used in [16]. In the cavity, the magnetic field pointed towards the EUV source as is indicated by the direction of 'B' in figure 1.…”
Section: Experimental Configuration and Methodsmentioning
confidence: 99%
See 3 more Smart Citations